Peer-relationship-problems account for quality of life impairments in pediatric psoriasis - Matterne, Uwe; Apfelbacher, Christian (Journal of psychosomatic research, 2016)
Objective - Most research on HRQoL-impairments in psoriasis has been conducted in adult patients, small pediatric patient samples or samples not representative of the pediatric population at large. We thus aimed to comprehensively describe HRQoL in pediatric psoriasis compared to psoriasis-free children and adolescents, identify domains most commonly affected and analyze its impact on HRQoL while controlling for important other predictors of HRQoL in a representative pediatric sample. - Methods - The impact of lifetime-prevalence of psoriasis on total and subscale HRQoL was analyzed by complex sample general linear models alone and adjusted for sociodemographic and clinical variables in a population-based sample (n=6518) of children and adolescents aged 11-17. - Results - Total HRQoL and the physical domain were significantly affected by lifetime-psoriasis in univariate analysis. In multivariate analyses, lifetime-psoriasis significantly impacted on total HRQoL and the subscale ‘quality of relationships with friends/peers’. Although substantial amounts of variance in HRQoL were explained by mental health, independent effects of lifetime-psoriasis remained after adjustment for this covariate. Total explained variance in total HRQoL was 20%. - Conclusion - Our findings suggest psoriasis to be a significant burden as it affects HRQoL even when controlling for mental health. Most of this effect appears to be driven by perceived impairments in the quality of relationship with friends/peers. How this exactly occurs needs to be explored in future research. Meanwhile clinicians need to be more attentive to this effect of psoriasis.